2021
DOI: 10.1111/1462-2920.15483
|View full text |Cite
|
Sign up to set email alerts
|

Soil actinobacteria tend to have neutral interactions with other co‐occurring microorganisms, especially under oligotrophic conditions

Abstract: Summary Actinobacteria produce a variety of secondary metabolites that can influence the survival or behaviour of other organisms. The understanding of the ecological roles of actinobacteria has significantly improved in the past decades, but a systematic insight into the interactions between actinobacteria and other microbes in nature is warranted. Here, we studied the pairwise effects of actinobacteria on other microbes isolated from red soils under different nutritional conditions. We found that neutral eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…The directionality itself is the qualitative outcome, i.e., the sign of the effect of one microorganism on another. Microbes can have net negative, neutral, or positive effect on one another and sometimes qualitative information of directionality may be sufficient to categorize interactions into relationship types and observe patterns (Yan et al, 2021). However, the strength, that is the quantitative magnitude of these effects, can vary and have important implications for the biodiversity and stability of microbial communities (Ratzke et al, 2020).…”
Section: Capturing Microbial Interactions While Accounting For Their Complex Naturementioning
confidence: 99%
“…The directionality itself is the qualitative outcome, i.e., the sign of the effect of one microorganism on another. Microbes can have net negative, neutral, or positive effect on one another and sometimes qualitative information of directionality may be sufficient to categorize interactions into relationship types and observe patterns (Yan et al, 2021). However, the strength, that is the quantitative magnitude of these effects, can vary and have important implications for the biodiversity and stability of microbial communities (Ratzke et al, 2020).…”
Section: Capturing Microbial Interactions While Accounting For Their Complex Naturementioning
confidence: 99%
“…Neutral interactions among bacteria are not frequently described. Nevertheless, a recent study reported dominance of neutral interactions among actinobacteria in the soil ecosystem (Yan et al, 2021), particularly in oligotrophic conditions, i.e., in nutrient poor conditions that resulted from obtained for each strain in each condition (single-strain or dual-strain biofilm). The detailed results obtained for biological replica are presented in Figure 3 and Figure S2.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the above four strains of MACB were chosen for subsequent co-culture. In addition, based on the antimicrobial activity and 16S rRNA gene similarity of the red soil-derived Streptomyces strains [19,24], 44 bioactive streptomycetes with abundant diversity were preferentially selected for this study (Table S1). The selected MACB and streptomycetes thus formed 176 (4 × 44) co-culture pairs.…”
Section: Preliminary Evaluation Of the Activation Ability Of Macb And Selection Of Red Soil-derived Streptomycetesmentioning
confidence: 99%
“…The strains used in this work are listed in Table S1. Eight MACB were isolated from soils collected in Haixi Mongolian and Tibetan Autonomous Prefecture, China [23], and two MACB and all Streptomyces strains were from red soils collected in Jiangxi Province, China [19,24]. All these strains were preliminarily identified by 16S rRNA gene sequencing in our previous studies [19,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation